Intellectual Capital Disclosure by the Listed Fuel & Power and Engineering Firms in Bangladesh - Hossain, Md. Mahabbat (Asian Accounting and Auditing Advancement, 2012)
The main objective of this study is to measure the level of intellectual capital (IC) disclosure practices by listed fuel & power and engineering companies in Bangladesh. Like physical assets, IC assets are also important for any organization. IC ensures the utilization of physical assets effectively and efficiently. Intellectual capital includes structural capital, relationship capital, and human capital. Having quality IC is the prerequisite for the smooth operation of an organization. But these important assets are not reported in the financial statement sufficiently or this information is not communicated to the stakeholders properly. The entity can enjoy competitive advantages in disseminating information regarding IC and stakeholders may make pragmatic decisions on the basis of this information as well. The profitability, potentiality, and sustainability of the organization may also depend on the quality of IC. The content analysis method is used in this study. An unweighted disclosure index, with 37 IC items, has been developed. The sample covers 80% of firms in the fuel & power and engineering industries. As a source of data, the corporate annual reports of the companies for the year 2007-2008 or 2008 were used in this study. Out of required items, average disclosure scores of human capital, structural capital and relationship capital are 37.94%, 64.81%, and 60.19% respectively. So, the average disclosure score of the sample complaints is 49.89%. The regression results show that the proportion of independent directors, the proportion of audit committee members, and market capitalization are influencing factors to disclose IC items in the annual reports.